Evaluation of relationship between interlead electrical delay time and reverse remodeling of left ventricle in patients with quadripolar cardiac resynchronization therapy for long-term follow-up. (14th October 2021) - Lubimceva, T; Chumarnaya, T; Lebedeva, V; Gasimova, N; Lebedev, D; Solovyova, O
Abstract: Background: Cardiac resynchronization therapy (CRT) has undoubtedly shown a high role in the treatment of advanced heart failure (HF). The effectiveness of CRT is individual and variable in each case. It is associated with the functional and structural features of heart as well as the dynamics of these features over time. Despite the quadripolar left ventricle (LV) lead widespread use, the problem of low response to CRT in the early and long-term remains actual. The search for predictors of the CRT response is an important scientific and practical issue. Purpose: To determine the relationship between the interlead electrical delay time and the CRT response during 24 month postoperative period. Materials and methods: We evaluated the clinical status, the quality of life and echocardiographic response of 37 patients with HF treated for 2 years with quadripolar LV lead CRT devices implanted according to guidelines: 25 males/12 females with age 62±10 years, 25 pts with history of ischemic cardiac disease, LVEF 26±7%; QRS duration 184±31 ms. The response to CRT was defined as 15% decrease of LV end-systolic volume (ESV). Interlead electrical delay time (EDT) was calculated automatically during CRT implantation, and subsequent 3–6-12–18–24 month follow-up. Results: The dynamic changes EDT and ESV were assessed for 24 months after CRT. There was a significantly higher average percentage of decrease of ESV in patients (n=18), in whom the stimulation of the LV lead was carried out from a pole having a maximum EDT, in 3 months (12±8% versus 10±6% p=0.021) and in 6 months (23±9% versus 18±9% p=0.003) after CRT. That was the dynamic of reverse remodeling is significantly higher in such patients for the first 6 months. Using logistic regression, it was shown that the relative decrease EDT in the first 3 months after CRT can be a predictor of outcomes in18 and 24 months after CRT with an accuracy of 71% and 77%, respectively. The greater the relative decrease EDT between 0 and 3 months, the greater the probability of a respond in 18 and 24 months after CRT. The cut-off threshold for determining the outcomes in 18 months was 18% on the balance of specificity and sensitivity equal to 80% and in 24 months was 15% on the balance of specificity and sensitivity equal to 90%. There were no differences between the HF etiology (ischemic/ non-ischemic) and baseline rhythm. Conclusion: The relationship between EDT and LV reverse remodeling have been investigated for 24 months. The rate of reverse remodeling is higher in patients in whom the stimulation of the LV lead was carried out from a pole having a maximum EDT. Relative decrease EDT in early period after CRT may be a predictor of the CRT outcomes in longtime period. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Russian Science Foundation